First principal study of structural, electronic, magnetic, thermodynamic, optical and thermoelectric properties of Nd(Co 1-x Fex)2 (x=0 to 1). (May 2023) - Ezaier, A.; Masrour, R.; Hamedoun, M.; Kharbach, J.; Rezzouk, A.; Hourmatallah, A.; Benzakour, N.; Bouslykhane, K.
Abstract: The structural, electronic, magnetic, thermodynamic, optical and thermoelectric properties of Nd (Co1-x Fex )2 compounds are studied using density functional theory (DFT), based on full-potential linearized augmented plane waves (FPLAPW), with the generalized gradient approximation (GGA) and GGA + U (with a Hubbard parameter "U"). The results obtained from the total magnetic moment equal to 17.73 μB /f.u. for Nd(Co0.5 Fe0.5 )2 alloy by the GGA method and 18.21 μB /f.u for the Nd(Co0.25 Fe0.75 )2 alloy in the case of GGA + U. The effects of temperature on some thermal properties are studied with the quasi-harmonic Debye model. The heat capacity CV converges towards a limit value of 148 J/mol.K. The optical and thermoelectric properties are studied. Indeed, the results show that the compound Nd(Co0.25 Fe0.75 )2 has a considerable value of static part of ε 1 (0) =  654, of the static refractive index n(0) = 28.0, of the reflectivity at zero frequency R(0) = 0.88 and optical conductivity of 10431(Ω.cm) −1 . Highlights: Magnetoelectronic and thermoelectric properties of Nd(Co1-x Fex )2 are studied. Effects of temperature on some thermal properties are studied with the quasi-harmonic Debye model. Heat capacity CV converges towards a limit value of 148 J/mol.K. Results show that the Nd(Co0.25 Fe0.75 )2 has a considerable value of static part of ε 1 (0). Static refractive index of the reflectivity at zero frequency and optical conductivity were found.